Interactive Video Animation Media Based on Problem Based Learning to Improve Students’ Motivation and Science Learning Outcomes - Sa'adah, Siti; Buchori, Achmad; Sulianto, Joko (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study aims to develop interactive video animation learning media with a Problem Based Learning (PBL) approach to improve students’ motivation and learning outcomes on the topic of plant reproduction in elementary school. The research employed a development method based on the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The media was designed using animation and interactive elements that visualize abstract biological concepts, supported by problem-based scenarios to encourage students’ critical thinking and engagement. The validation process involved media experts, material experts, and learning design experts. The results indicated that the media met the “very valid” category, with an overall average score above 90%. Practicality tests conducted with teachers and students showed excellent usability, with mean scores of 95% and 94%, respectively, indicating that the media was easy to operate and engaging. The effectiveness test using a pretest-posttest control group design demonstrated significant improvements in both motivation and learning outcomes, as evidenced by an N-Gain score of 0.70 and a significance value of 0.000 < 0.05. These findings suggest that the developed interactive video animation media is valid, practical, and effective for enhancing students’ motivation and achievement in science learning. The integration of PBL and digital animation provides meaningful learning experiences, supports active participation, and contributes to innovative instructional practices in the context of the Merdeka Curriculum implementation in elementary schools.